MEDIA LITERACY CAPABILITY STUDENTS IN DEALING WITH HOAX NEWS ON SOCIAL MEDIA - Ivanka, Chika Maya; Batubara, Abdul Karim; P, Indira Fatra Deni (Academic Solution Publisher, 2023)
This study aims to determine the ability of SMA Negeri 1 Bandar students to analyze hoax news on social media, the ability of SMA Negeri 1 Bandar students to access hoax news on social media, the ability of SMA Negeri 1 Bandar students to evaluate hoax news on social media, and the relationship between media literacy skills. SMA Negeri 1 Bandar students in tackling hoax news on social media. This study uses quantitative research methods using questionnaires or questionnaires as a means of collecting data obtained from respondents. The population of this study were students of class XI majoring in science and social studies as many as 418 students with a total sample of 80 students who were determined by the slovin formula. The sampling technique used to determine the sample is purposive sampling. To measure the relationship between the media literacy abilities of SMA Negeri 1 Bandar students in tackling hoax news on social media and test hypotheses using the Spearman's Rho Rank-Order Correlations formula and Guilford's calculations. The results showed that media literacy ability has a positive relationship with a value of 0.894 which indicates a high relationship in tackling hoax news